RISK FACTORS PULMONARYTUBERCULOSIS IN POASIA HEALTH CENTRES IN THE COASTAL REGION OF KENDARI CITY: PULMONARYTUBERCULOSIS - Ifon Ifon; Timbul Supodo; Sunarsih Sunarsih; Sanihu Munir; Azis Harun (STIKes Mandala Waluya Kendari, 2021)
Introduction:Tuberculosis or pulmonary tuberculosis is an infectious disease caused by the presence of the bacteria Mycobacterium Tubercolusis. Tuberculosis is a health problem. Kendari City prevalence is 3.53 per 1,000 population, especially in the work area of ??the Puskesmas Poasia, coastal area of ??Kendari City, every year there is a decrease, namely in 2017 as much 51 cases of lung TB smear positive, in 2018 as many50 cases of smear positive pulmonary TB and in 2019 as many49 cases of smear positive. However, this has not yet been able to achieve the National target, which is a minimum cure rate of 85%.The research objective was to determine the risk factors for the incidence of smear positive pulmonary TB inPuskesmasPoasia in the coastal area of ??Kendari City. Methods: This type of research is a case control Study conducted from December 2020 to January 2021, the sample used are 30 cases taken by random sampling and 30 controls. Result: Using Odds Ratio (OR). OR valuehabit of cleaning mosquito nets OR = 9,036> 1, cleaning or drying bedding or mattress OR = 6,571> 1, Drop Out Treatment nno OR value, humidityOR = 6.909> 1, sunlight lighting OR = 5,675> 1and home ventilationOR = 4.030> 1. Conclusion: Habit of cleaning mosquito nets, cleaning or drying bedding or mattress, moisture, sunlight lighting and home ventilation is a risk factor meanwhile drop out treatmentis not a risk factor for the incidence of smear positive pulmonary TB in PuskesmasPoasia in the coastal area of ??Kendari City.